The Neighbourhood Unit in Late Colonial Angola: Concentration Repertoires and Urban Policies (1950–1974) - Pinto da Cruz, Bernado (Comparativ, 2020)
During Angola’s late colonial period, Portuguese elites tried to put forward and bring together two antagonist means of social control: repression and welfare. While villagization schemes were being deployed across the hinterland, a new form of urban management was taking place at the suburban areas of Luanda, the musseques. This article unearths the links between penal concentration, rural resettlement and slum management, by examining the colonial reception of and the political and professional struggles around the urban design notion of “neighbourhood unit” in Angola. The colonial revival of a concept that was falling into discredit in the “developed world” was critical to legitimize the urban appeal of a rural extractive institu- tion – village concentration – and its deployment in the urban milieu. In Angola, state coercion became integral both to the development of permanent housing and the social knowledge the former entailed.